Current state and prospects of using dendritic cell vaccination for cancer immunotherapy - I.Yu. Filin; K.V. Kitaeva; A.A. Rizvanov; V.V. Solovyeva (Учёные записки Казанского университета: Серия Естественные науки)
Recent advances in cancer immunotherapy have steadily increased the effectiveness of standard antitumor therapy methods. Due to their low toxicity and simple production process, personalized therapeutic vaccines based on dendritic cells are of particular clinical interest. A striking fact is that the first attempts to use such vaccines in clinical practice were discouraging. However, their scope and effectiveness were subsequently greatly enhanced by the development of new approaches to activating and loading dendritic cells with tumor-associated antigens, as well as by their use as an adjuvant in combination with other therapeutic methods for cancer treatment. This review considers new techniques and the latest achievements in the development of dendritic vaccines that ensure their clinical success.